Investigation and molecular Identification of circulating foot-and-mouth disease virus serotypes in the Duhok province- Kurdistan of Iraq - Ahmed, Jivan Qasim; Ahmed, Meqdad Saleh; Khanamir, Ramadhan Ado (Sulaimani Journal for Pure and Applied Sciences, 2018)
Foot and mouth disease virus (FMDV) is considered as one of highly contagious and economically devastating viral infection of cloven-hoofed animals in Iraq. This study was performed to investigate the molecular characterization and typing of the current outbreak of FMDV in Duhok province of Kurdistan- Iraq. A total of 15 epithelial samples were taken from clinically infected calves. These samples were subjected to RNA extraction and RT-PCR for the purpose of typing and detection as well as sequencing and phylogenetic analysis. All of 15 samples was positive for FMDV and detected as serotype O by multiplex RT-PCR. Furthermore, the sequences were shown a close relationship with Panasia topotype. The limitation of these monitoring studies is that the partial sequencing is not adequate to monitor the circulating strain as it might hide some important changes unsequenced, therefore the investigation of inclusion of complete gene of VP1 protein is highly recommended to get a complete picture of potential mutation on that immunogenic protein.
Keywords: FMD serotype O; partial VP1 sequencing; Kurdistan of Iraq